Describe the various aspects of climate change, including temperature fluctuations, changes in precipitation patterns, and increased frequency of extreme weather events - Garg, Ram Kumar; Chinchorkar, Sachin Shrikant; Rao, L Malleswara; Janardhan, Gadekar Deepak; Garg, Akansh (Journal of Neonatal Surgery, 2025)
Climate change is a very concerning global issue that involves considerable changes in the climate system of Earth, most of which are caused by human activities like fossil fuel combustion and deforestation. Rising global temperatures if anything, amounting to roughly 1.2°C higher by the pre-industrial era, along with heat waves, glacial melt, and sea level rise are the key manifestations. The patterns of precipitation are also skewed—the rainfall is intensified in one region while others endure lengthy drought and the agriculture and water resources are impacted. In addition, the frequency and severity of extreme weather events like hurricanes, floods, wildfires, and droughts have escalated, and that has caused wide damage to ecological, economic, and social areas. The threat of these changes to food security, biodiversity, human settlements, notably in vulnerable areas, is high. Combating these impacts requires mitigation strategies of reducing greenhouse gas emissions and adopting renewable energy, and adaptive measures of resilient infrastructure. We need to understand the manifold nature of climate change, so that policymakers, scientists and the local communities develop effective ways and ways to combat the change and protect future generations